Pengaruh Pengendalian Kerja Terhadap Kinerja Karyawan PT. Koyorad Jaya Indonesia - Kurniawan, Toni; Adriza, Adriza; Wibowo, Hadi Mulyo (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Employee performance is a critical factor in achieving organizational goals, and work control plays an important role in ensuring that performance standards are met. However, in many organizations, including PT. Koyorad Jaya Indonesia, issues such as unclear job descriptions, weak discipline, and limited communication between superiors and subordinates have been observed, potentially hindering optimal performance. This study aims to examine the effect of work control on employee performance at PT. Koyorad Jaya Indonesia. A quantitative approach with descriptive and verification methods was applied, using a structured questionnaire distributed to 46 active employees. The data were analyzed through validity, reliability, descriptive statistics, correlation, and determination tests. The findings reveal that both work control and employee performance are rated in the “very good” category, with mean scores of 4.59 and 4.62, respectively. Furthermore, the coefficient of determination indicates that work control contributes 71.9% to employee performance, while the remaining 28.1% is influenced by other factors not included in this study. These results highlight the strategic importance of effective work control in improving employee performance, suggesting that management should strengthen control practices to sustain productivity and efficiency.